Traditional Chinese herbs and natural products in hyperuricemia-induced chronic kidney disease - Yang, Letian; Wang, Bo; Ma, Liang; Fu, Ping (Frontiers in Pharmacology, 2022)
Hyperuricemia is a common biochemical disorder, which resulted from both excessive uric acid (UA) production and/or absolute or relative impairment of urinary UA excretion. Growing evidence indicated that hyperuricemia was an independent risk factor for the development and progression of chronic kidney disease (CKD), causing hyperuricemia-induced CKD (hyperuricemic nephropathy, HN). The therapeutic strategy of HN is managing hyperuricemia and protecting kidney function. Adverse effects of commercial drugs make persistent treatment of HN challenging. Traditional Chinese medicine (TCM) has exact efficacy in lowering serum UA without serious adverse effects. In addition, TCM is widely applied for the treatment of CKD. This review aims to provide an overview of efficacy and mechanisms of traditional Chinese herbs and natural products in hyperuricemia-induced CKD.